Landscape of Possibility Community Filmmaking in Indonesia as a Relational Process - Engchuan, Rosalia (Bijdragen Tot De Taal- Land- En Volkenkunde, 2021)
This essay is driven by the question of how Candra, the writer and director of Dewi pulang (2017), is able to sustain his cinematic practice, despite the controversial nature of his films. Considering the notion of landscape of possibility, this essay traces processes that precede and go beyond the production of a particular film, but which are nevertheless constitutive of its becoming. These entanglements are explored through concrete stories in dialogical engagement with film practitioners in Indonesia. Adding these to the conversation of what constitutes a film conceptually and analytically, the desired gesture of this essay is less a representation or documentation of Candra's practice or Indonesian film communities but rather a provocation to approaches in film studies that operate on binary assumptions of landscape as an external backdrop (of text and context, film and maker, state and film production). I will argue that the evolution of film communities in Indonesia challenges commonly held assumptions about the role of the state in `independent' film, and the linear `assembling logic' from `grassroots' to `mainstream'.
CRIS-Team WoS Importer:2021-07-23